Heterogeneity in diagnostic characters across ecoregions: A case study with Botrynema (Hydrozoa: Trachylina: Halicreatidae) - Montenegro, Javier; Collins, Allen G.; Hopcroft, Russell R.; Questel, Jennifer M.; Thuesen, Erik V.; Bachtel, Tiffany S.; Bergman, Leah A.; Sangekar, Mehul N.; Drazen, Jeffrey C.; Lindsay, Dhugal J. (Frontiers in Marine Science, 2023)
Gelatinous zooplankton are ubiquitous and common in the oceans from estuaries to abyssal depths. However, the diversity of the gelatinous community is often underestimated. It is thought that a significant part of their diversity might be composed of cryptic species. Medusozoans are one of the main components of gelatinous communities. Botrynema, a genus of medusozoans in the trachyline family Halicreatidae, currently contains two species: B. brucei and B. ellinorae, distinguished by the presence or absence, respectively, of an apical knob as a diagnostic character. However, no study has corroborated if these taxonomic diagnoses have a biological and evolutionary basis. Therefore, in this study we attempted to address the question “do the two nominal species in the genus Botrynema represent independent phylogenetic lineages, or two phenotypic variants of a single species?” In this study we took advantage of legacy collections from different research expeditions across the globe since 2000 to 2021 to study the phylogenetics and taxonomy of the genus Botrynema. Based on the evidence we gathered, we conclude that while the genus Botrynema does contain at least two species lineages, these lineages are not concordant with current species definitions. The species B. ellinorae is reassigned as a subspecies of B. brucei and diagnostic characters are provided.